Effectivitas infusum daun durian Durio zibethinus sebagai anestesi alami ikan bawal air tawar Colossoma macropomum - Aris Munandar; Ginanjar Trisno Habibi; Sakinah Haryati; Mas Bayu Syamsunarno (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2017)
The use of chemicals as an anesthetic can leave residues in the body of the fish and gave the negative impact to the human who consumed this fish. Therefore, the exploration of natural anesthesia as an alternative is crucial. One of the natural products that can be used is the leaves of durian. The purpose of this study was to determine the best concentration of the durian infuse for tambaqui anesthesia and the optimum time of transportation. This research was conducted in several two stages; extraction leaves durian and simulation of transport fish with a dry system using respective concentration of durian infuse. The tested concentrations of durian infuse were; 0 ppm, 1000 ppm, 2500 ppm, 5000 ppm, 7500 ppm, and 10000 ppm The study showed that the best concentration of durian leaf extract infused amounted to 5900 ppm. These concentrations resulted in fainting fastest time for 100 minutes, and the time conscious of 1 minute 30 seconds. Dry transport time that produces the best survival rate was approximately 2 hours with the survival rate of 83.3%.Penggunaan bahan kimia sebagai anestesi dapat meninggalkan residu dalam tubuh ikan dan berdampak negative pada manusia yang mengkonsumsi. Oleh karena itu, penggunaan bahan anestasi alami dapat digunakan sebagai alternatif untuk mengatasinya. Salah satu bahan alami yang dapat digunakan adalah daun durian. Tujuan penelitian ini adalah untuk menentukan konsentrasi dan waktu transportasi terbaik dari infusum daun durian sebagai bahan anestesi. Penelitian ini dilakukan dalam dua tahap, yaitu pembuatan infusum daun durian dan simulasi transportasi ikan dengan sistem kering. Konsentrasi infusum yang diuji adalah 0 ppm, 1000 ppm, 2500 ppm, 5000 ppm, 7500 ppm and 10000 ppm Konsentrasi terbaik infusum daun durian adalah sebesar 5900 ppm. Konsentrasi tersebut dapat menghasilkan waktu pingsan tercepat selama 100 menit, dan waktu sadar 1 menit 30 detik. Waktu transportasi kering yang menghasilkan survival rate terbaik terdapat pada jam ke 2 yaitu sebesar 83,3%.